Assessment of Alertness and Cognitive Performance of Closed Circuit Rebreather Divers with the Critical Flicker Fusion Frequency Test in Arctic Diving Conditions - Piispanen, Wilhelm (My University, 2021)
The aim of our study was to research the effect of cold water on the cognition of Finnish technical diving population using the Critical Flicker Fusion Frequency (CFFF) -test. We also studied the effect of breathing gases containing helium on cognition, subjective feeling of cold and on measured temperature of skin. There have not been any CFFF-studies in arctic conditions with a study-setup comparable to ours. Most of the CFFF-studies pertaining to hyperbaric medicine have been conducted in pressure chambers and there are only a handful of studies in open water. 23 subjects performed an identical dive with a controlled trimix gas in an ice- covered water filled quarry. The subjects assessed their thermal comfort at four time points during the dive. In addition, their skin temperature was measured at 5-min intervals throughout the dive. The divers performed the CFFF test before the dive, at target depth, and after the dive. The CFFF-values showed a statistically significant increase to 111.7% during the dive compared to the pre-dive values (p<0.0001). The values returned to pre- dive values after the dive. In previous studies, a similar profile of CFFF-values has been noted. The divers’ skin temperatures showed a statistically significant decrease during the dive (p<0.001). The subjective temperature also decreased during the dive (p=0.01). The results of our study seem to indicate that cold water environment, or breathing gases containing helium have no effect on the profile of the CFFF-values.
Keywords: sukelluslääketiede, anestesiologia, Critical Flicker Fusion Frequency, arktinen ympäristö